Eating behavior, body self-perception and nutritional status of nutrition students (Research, Society and Development, 2022)
The knowledge acquired during the undergraduate nutrition course can impact the eating behavior and perception of the body image of its students, so the objective of the research was to evaluate the nutritional status, eating attitudes and identify their body perception in undergraduates of the course. of nutrition, being a descriptive, transversal, epidemiological-nutritional and behavioral research, with data collection from a form containing socioeconomic data, Food Attitudes Scale (EAAT) and Silhouette Scale. Statistical analysis was performed using the SPSS online version, considering p